Transnational traders: El Salvador’s women couriers in historical perspective - Garni, Alisa M. (My University, 2014)
An estimated one-third to one-half of Salvadorans who carry remittances and goods between El Salvador and the United States are women. Scholars studying these viajeras argue that their work simultaneously represents a break from traditional gender relations confining women to the home and an extension of gender traits that favor women in developing social ties. Although social ties are crucial to the courier trade, this argument ignores antecedents to viajeras’ work in El Salvador and suggests that transnationalism pushes women into realms of labor and physical mobility that have been gendered masculine. Using ethnographic methods, I examine the relationship between women’s historical work in El Salvador and their current work as viajeras, as well the relationship between viajeras’ experiences and those of women transnational traders in other parts of the world. My findings contribute to a small but growing body of research suggesting that instead of merely being excluded from or manipulated by global processes, many women in the Global South have expanded the realm of their activities to help shape variable forms of global capitalism. Studying how they do so sheds light on local mechanisms for combating gender inequality and promoting development.
Keywords: Migration; Development; Gender; Transnational couriers; El Salvador; Central America